Políticas de ciencia, tecnología e innovación hacia atrás, hacia adelante y más allá: retos y oportunidades de desarrollo para Iberoamérica en la era de COVID -19 - Isabel Álvarez; José Miguel Natera; Diana Suarez (Revista de Economía Mundial, 2020)
This article explores challenges and opportunities for science, technology and innovation (STI) policy in Ibero-America related to the COVID-19 pandemic, considering a multidirectional approach that combines: (i) transversality, for national innovation systems (NIS) integration with other subsystems; and (ii) coordination of STI across national and international spaces. We claim that a new approach to STI policy is required. Departing from the situation of the region, the sanitary and economic crisis, and the evolution of NIS and policy rationale, we propose some guidelines for a new STI policy agenda based on the region’s challenges ahead and the need for mechanisms of coordination.